2010
DOI: 10.1007/s00299-010-0942-5
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of human interferon alpha-2b in transgenic carrot (Daucus carota L.) plants

Abstract: In this study, we report the obtaining of carrot plants expressing human interferon alpha-2b via Agrobacterium-mediated transformation using two vector constructs containing the sequence coding for interferon gene fused with Nicotiana plumbagenifolia calreticulin apoplast targeting signal driven by 35S CaMV promoter and root-specific Mll promoter. The human interferon alpha-2b gene was correctly translated in carrot plants according to Western blot analysis. The recombinant protein exhibited antiviral activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Such a result might be expected, since there is the ifn α2b gene under the control of root specific promoter Mll in vector pCB161 used for transformation [32]. However, previously, using the same vector, it was revealed that the active α2b inter feron was synthesized not only in carrot roots, but also in the carrot leaves [12]. Perhaps, the effect of the Mll promoter is species specific.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Such a result might be expected, since there is the ifn α2b gene under the control of root specific promoter Mll in vector pCB161 used for transformation [32]. However, previously, using the same vector, it was revealed that the active α2b inter feron was synthesized not only in carrot roots, but also in the carrot leaves [12]. Perhaps, the effect of the Mll promoter is species specific.…”
Section: Resultsmentioning
confidence: 86%
“…Genetic transformation using bacteria of the Agro bacterium genus is often applied to obtain transgenic plants, including those with IFN genes [12,29], since these bacteria have a natural ability to transfer their own DNA into plant cells (in nature, this is the forma tion of "crown galls" when infected by A. tumefaciens or "hairy" roots when infected by A. rhizogenes). This genetic transformation method is quite simple, requires no special equipment, and can be used for the transformation of different plant species [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are the subject of the article by Zhang et al (2011) which focuses on the example of tomato, while Sato et al (2011) address the problem of chilling tolerance in rice. The problem of expressing pharmacologically active peptides in plants is addressed in the study by Luchakivskaya et al (2011) and Soria-Guerra et al (2011). Finally, Subramanyam et al (2011) and Basnayake et al (2011) present progress towards the transformation of banana and diverse sugarcane cultivars, respectively.…”
mentioning
confidence: 99%